Perancangan Sistem Administrasi Dokumen Asuransi - Djatmika, Gatot Hery; Ningsih, Putu Tirta Sari; Harsono, Budi; Abdullah, Mohammad Taufiq (Universitas Mohammad Husni Thamrin, 2023)
Penelitian ini menginvestigasi dan merancang